Homeless and powerless : child victims of sexual exploitation - Shamim, Ishrat; Chowdhury, Quamrul Ahsan (Dhaka, Bangladesh : Bangladesh Sociology Association, University of Dhaka, 1993)
With special reference to Bangladesh.
Includes bibliographical references (p. [69]-70).
Momiul
Keywords: Child sexual abuse -- Bangladesh; Child prostitution -- Bangladesh; Child sexual abuse -- Developing countries; Child prostitution -- Developing countries; Children's rights -- Bangladesh